β2-adrenergic stimulation blunts inhibition of epithelial ion transport by hypoxia of rat alveolar epithelial cells - Löh, Benjamin; Baloglu, Emel; Ke, Alberto; Bärtsch, Peter; Mairbäurl, Heimo (Cellular physiology and biochemistry, 2010)
Hypoxia impairs alveolar fluid clearance by inhibition of Na+ reabsorption, and also impairs β2 adrenergic signaling in alveolar epithelium. Since both are major rescue mechanisms preventing pulmonary edema, we studied whether acute and prolonged treatment with terbutaline would prevent hypoxic inhibition of ion transport.
Online veröffentlicht am 22. Dezember 2009
Gesehen am 29.03.2023